Assessment of general movement among infants not at risk of developmental delay (Journal of Medical Science, 2020)
Introduction. The functional assessment of general movements (GMs) is a common test for the developing nervous system. The high predictive validity of abnormal GMs for cerebral palsy has been documented among preterm infants. Aim. The present study examined whether term infants without any documented risk factors for neurodevelopment delay may benefit from an assessment of GMs. Material and Methods. One hundred and four infants ranging in age from 1–4 months were evaluated using Prechtl’s method, of which, thirty-eight were younger than two months of age and the remaining sixty-eight were older than two months of age (with available detailed neonatal characteristics). The following movements were considered among younger infants, writhing, poor repertoire and cramped synchronised, whereas fidgety, cramped synchronised, poor repertoire, chaotic and abnormal GMs were evaluated in older infants. Infants were classified as ‘normal’ or ‘abnormal’ groups based on their presenting GMs. We determined postural positional preference, following Kaplan recommendations, with features categorised as either ‘present’ or ‘absent’, as well as activity level and general muscle tone (‘normal’ or ‘abnormal’). Results. Cramped synchronised GMs were observed in seven (18.4%) younger infants and in eleven (16.7%) older infants. There was no difference in the clinical characteristics of children with normal vs. abnormal GMs. Abnormal muscle tone was associated with a higher OR (p = 0.0039) of presenting with abnormal GMs (4.6063; 95%CI: 1.6303–13.0149). Although the infants studied were not at risk for developmental disorders, almost one-fifth required follow-up neurological consultation. Conclusions. An assessment of GMs should be considered as a universal screening tool among healthy infants without risk factor(s) for developmental deficits.